2020
DOI: 10.1093/asj/sjaa309
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of Common Antimicrobial Solutions Used for Breast Implant Soaking and Breast Pocket Irrigation—Part 1: Efficacy Against Planktonic Bacteria

Abstract: Background Planktonic bacteria can be inadvertently introduced during breast surgery procedures, which are hypothesized to lead to complications such as infection, capsular contracture, BIA-ALCL, and a prolonged local inflammatory response. The use of antimicrobial solutions such as triple antibiotic solution (TAB) and/or 10% povidone-iodine (PI), in breast pocket irrigation or implant soaking have been proposed to reduce planktonic bacterial attachment and potential complications. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 42 publications
0
10
1
Order By: Relevance
“…Treatment with PI can also elicit cytotoxic effects on healthy cells 27-30 and, as such, some clinicians dilute PI to avoid these effects while mitigating bioburden. However, as noted in our results and in contrast to the results of our planktonic bacteria study, 45 diluting PI lower than quarter-strength will likely minimize its efficacy against biofilm-associated bacteria.…”
Section: Discussioncontrasting
confidence: 81%
See 3 more Smart Citations
“…Treatment with PI can also elicit cytotoxic effects on healthy cells 27-30 and, as such, some clinicians dilute PI to avoid these effects while mitigating bioburden. However, as noted in our results and in contrast to the results of our planktonic bacteria study, 45 diluting PI lower than quarter-strength will likely minimize its efficacy against biofilm-associated bacteria.…”
Section: Discussioncontrasting
confidence: 81%
“…epidermidis may be the most tolerant species to PI, which is consistent with the results of our study with planktonic bacteria. 45 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…57 However, newer in vitro studies have found that povidone-iodine only or povidone-iodine containing triple-antibiotic solutions are more effective at significantly decreasing planktonic species and biofilm production. 60,61 In addition to irrigating the breast implant pocket, these solutions can also be injected into the implant packaging to address potential bacterial attraction due to an electrostatic charge imparted on opening the sterile package. 35 Layered closure of the incision must be performed to prevent implant exposure or inadvertent contamination.…”
Section: Surgical Techniquementioning
confidence: 99%